Mujeres, cárceles y drogas = Women, prisons and drugs - Almeda Samaranch, Elisabeth (Oñati Socio-Legal Series, 2012)
This article aims to highlight the discrimination suffered by women prisoners in our country, in particular, of those incarcerated for its direct or indirect relationship with drugs. First we draw a radiography describing women in Spanish prisons, presenting general data, reasons for the high rates of female incarceration, sentences and types of crimes committed by women prisoners, either foreign or nationals, to clearly demonstrate that the drug issue cuts across all these aspects. Secondly, we will discuss the evolution of the Spanish penal law relating to offenses against public health, especially in recent months, in which there has been a significant change in terms of the sentences that are being applied to women. And finally, it will bring up some data on the prevalence of drug use in prisons and treatments developed in them.